Biodiversity of ophiuroids (Echinodermata: Ophiuroidea) from the slope of the Yucatan Peninsula, Mexico - Durán-González, Alicia; Laguarda-Figueras, Alfredo; Solís-Marín, Francisco-Alonso; Gracia, Adolfo; Vázquez-Bader, Ana Rosa (Revista de Biología Tropical, 2021)
Introduction: The Ophiuroidea class is the most diverse of the Phylum Echinodermata, with 2 064 described species, which can be found from intertidal zones to abyssal depths, but the fauna of Yucatan peninsula needs more study. Objective: To describe the diversity of ophiuroids in the Yucatan continental slope. Methods: Information was compiled from four oceanographic surveys carried out in August 2005, June 2007 (BIOREPES 1 and 2: BRP1 and BRP2), April 2011 and August 2014 (COBERPES 2 and 6: CBP2 and CBP6). The specimens were obtained by trawling with a shrimp net in soft substrates and with a skimmer-type trawl dredge at a depth range of 200 to 1 071 m off the states of Yucatán and Quintana Roo, Mexico. Results: We found members of two superorders, five orders, six suborders, five superfamilies, 18 families, 28 genera and 43 species. Conclusions: The northeast zone Yucatan Peninsula has at least 43 species, of which 19 are new records for the area.